Application of a 3D printed wig protection device after decompressive craniectomy - Shasha Ma; Chenglong Li; Yue Gu; Yang Chen; Xuexin Li; Qingbo Wang; Hongmei Xu (Scientific Reports)
Abstract Wig protectors produced via 3D printing were used in skull protection protocols following decompressive craniotomy (DC) surgery. This study is a single-center, prospective trial involving 25 patients who underwent DC. Patients admitted between February 1, 2023, and June 30, 2023, were assigned to the control group (receiving standard care), while those admitted between July 1, 2023, and December 31, 2023, comprised the experimental group (receiving 3D-printed wig protection). The study evaluated participants based on various metrics, including reinjury at the site of the skull defect, daily wear duration, skin indentation, pain levels, itching, discomfort, patient-reported aesthetics, and the Quality of Life (QLQ-C30). They completed both wear assessments and follow-up evaluations at 1, 4, 8, and 12 weeks. Post-intervention, the experimental group exhibited a lower incidence of secondary injuries compared to the control group (0 vs. 3, P = 0.206). At the three-month follow-up, the experimental group demonstrated better outcomes in self-assessed aesthetics (P = 0.025) and QLQ-C30 scores (P = 0.041). The 3D-printed wig protector had a weight of 132.3 ± 11.98 g (ranging from 111 to 146 g), and none of the patients in the experimental group reported pain, pressure, itching, or discomfort during the first 30-min wear period. On average, patients wore the device for 2.01 ± 0.22 h in week 1, 5.71 ± 0.40 h in week 4, 6.04 ± 0.10 h in week 8, and 5.93 ± 0.47 h in week 12. While some patients reported minor skin indentation, pain, itching, or a sensation of stuffiness, no serious adverse events were observed.